Konsep Mencari Ilmu Dengan Metode Muṭāla’ah, Mużākarah, Munāżarah (Kajian Kitab Waṣāyā Al-Ābā’ Lil Abnā’ Karya Syaikh Muhammad Syakir) - Nada, Izza Shoffa; Nur Amin, Muhammad Yusuf; Fatkhurrohman (DAS Institute, 2024)
This article aims to examine the concept of seeking knowledge using the Muṭāla'ah, Mużākarah, Munāżarah method in the book Wasāyā Al-Ābā' Lil Abnā' by Shaykh Muhammad Syakir and how to contextualize seeking knowledge using the Muṭāla'ah, Mużākarah, Munāżarah method in the book Wasāyā Al-Ābā' Lil Abna'. The author uses a qualitative approach through libraries (Library Research) to collect data obtained through books, literature and online media, so the library method data collection is scientific in nature which comes from primary data and secondary data.The results of this research are: First, the concept of seeking knowledge in the book Wasāyā Al-Ābā' Lil Abnā', the importance of knowledge from various spiritual, moral and intellectual dimensions in seeking knowledge. There are 4 concepts in seeking knowledge, namely: the importance of seeking knowledge, goals in seeking knowledge, utilizing time, obstacles to seeking knowledge. Second, the concept of the Muṭāla'ah, Mużākarah, Munāżarah method in seeking knowledge, the Muṭāla'ah Method, if you want to get goodness and blessings then keep deliberating and learning even though you already understand. Mużākarah method, keep reviewing the lessons that have been studied so that they are firmly in your memory and avoid forgetting. The Munāżarah method, respecting each other's opinions when discussing and maintaining etiquette are important. Third, contextualize the concept of seeking knowledge using the Muṭāla'ah, Mużākarah, Munāżarah method in the book Wasāyā Al-Ābā' Lil Abnā': a) contextualization of the concept of seeking knowledge in this book, we as the young millennial generation should be able to pay attention to steps to seek knowledge that not only develop logic, but also worship that has certain rules, manners, goals and methods. b) contextualization of the Muṭāla'ah, Mużākarah, Munāżarah methods in this book, 1) Muṭāla'ah method, which includes independent learning, overcoming forgetfulness, strengthening literacy, and the use of digital technology. 2) Mużākarah Method, which includes collaborative learning, developing soft skills, increasing understanding of concepts through discussion. 3) Munāżarah method, which includes formal education, informal education and social life.